1992
DOI: 10.1104/pp.100.1.502
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Phosphate Synthase and Sucrose Accumulation at Low Temperature

Abstract: The influence of growth temperature on the free sugar and sucrose phosphate synthase content and activity of spinach (Spinacia oleracea) leaf tissue was studied. When plants were grown at 25 C for 3 weeks and then transferred to a constant 5 C, sucrose, glucose, and fructose accumulated to high levels during a 14-d period. Predawn sugar levels increased from 14-to 20-fold over the levels present at the outset of the low-temperature treatment. Sucrose was the most abundant free sugar before, during, and after e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
207
0
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(229 citation statements)
references
References 41 publications
17
207
0
5
Order By: Relevance
“…In all species except Trifolium, the rise in leaf TNC found was primarily the result of an increase in sugars that, however, was moderate compared to the high sugar levels already observed under ambient CO 2 . Such high natural sugar concentrations in leaf tissue have often been found in cold-adapted plants (Mooney & Billings 1965;Pollock & Lloyd 1987) and are known to be correlated with frost resistance (Sakai & Larcher 1987;Guy, Huber & Huber 1992). The moderate rise in sugar concentration under elevated CO 2 may still increase cold hardiness.…”
Section: Nitrogen Concentrations and Nitrogen Pools In The Biomass Pementioning
confidence: 99%
“…In all species except Trifolium, the rise in leaf TNC found was primarily the result of an increase in sugars that, however, was moderate compared to the high sugar levels already observed under ambient CO 2 . Such high natural sugar concentrations in leaf tissue have often been found in cold-adapted plants (Mooney & Billings 1965;Pollock & Lloyd 1987) and are known to be correlated with frost resistance (Sakai & Larcher 1987;Guy, Huber & Huber 1992). The moderate rise in sugar concentration under elevated CO 2 may still increase cold hardiness.…”
Section: Nitrogen Concentrations and Nitrogen Pools In The Biomass Pementioning
confidence: 99%
“…Proteins were extracted by grinding lyophilized material (1 g) in 5 ml of ice-cold 3-(N-morpholino) propane sulphonic acid (K + ) buffer (0n05  ; pH 7n5), containing 10 m MgCl # , 1 m EDTA, 5 m DTT, 0n1% (v\v) Triton-X2 100 (Boehringer, Mannheim, Germany) and 1 % (w\v) insoluble polyvinylpyrrolidone (Guy, Huber & Huber, 1992). The homogenate was centrifuged (13 000 g, 10 min) and the proteins in the resulting supernatant were precipitated with ammonium sulphate (70 % saturation) according to Mu$ ller, Boller & Wiemken (1996).…”
Section: Enzyme Assays and Protein Determinationmentioning
confidence: 99%
“…As the temperature decreases, the activity of SS and SPS is reduced, but it is estimated that it will maintain a high activity under natural conditions from the beginning of November 2016 to the end of February 2017. Previous studies have shown that the enzyme activities involving sucrose metabolism maintain a certain activity at low temperatures (Guy et al, 1992). of different varieties of sweet sorghum straw was not exactly the same (Lingle, 1987).…”
Section: Discussionmentioning
confidence: 99%